Influence of the shape of the electrodes on the tunnel current: Электpонные свойства металлов и сплавов - Keijsers, R. J. P.; Voets, J.; Shklyarevskii, O. I.; Kempen, H. van (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
The tunnel resistance of highly stable, mechanically controlled break junctions of Al, Au, Cu, Pb, Ni, Pt, and Pt-Ir, have been recorded as a function of the electrode spacing over 6-7 decades. Clear deviations from the expected exponential behavior have been observed. Comparison with previous experimental and theoretical studies indicate that the discussed deviations in some cases are most probably due to the shape of, rather than to interactions between, the two electrodes.